Does the green credit policy promote the technological innovation of clean energy enterprises? Empirical evidence from China - Gu, Xuesong; Tian, Zehua (Frontiers in Energy Research, 2023)
The aim of this paper is to examine the impact of green credit policies on the technological innovation of clean energy enterprises. Constructing quasi-natural experiments during two different lengths of period, a group of A-share listed clean energy enterprises and non-clean energy enterprises were selected as samples. The results show that green credit policies can promote technological innovation for clean energy enterprises, and this effect is reinforced with the accumulation of years following policy implementation. The mechanism test indicates that green credit policies affect the level of technological innovation of clean energy enterprises through credit cost and financing constraints. The heterogeneity analysis demonstrates that the impact of green credit policies is more significant in the non-state-owned enterprises and economically developed regions. The results provide insights for the promotion of green credit policy and the ultimate transformation of China's energy structure, thus providing reference for developing countries and emerging economies.